Multi-objective bike-way network design problem with space–time accessibility constraint - Zhu, Siying (2022)
This paper investigates a bike-way network design problem for retrofitting existing cycling infrastructure for commuter cyclists. A multi-objective integer linear programming model is formulated to determine the spatial layout of bike-way networks and types of bike-way links. The objective of the formulation is to maximize the accessibility, minimize the number of intersections, maximize bicycle level of service, and minimize total construction cost subject to space–time constraint and monetary budget. In the formulation, the accessibility measure considers not only connectivity, but also cyclists’ travel time budget between each origin-activity location pair. The problem is solved by augmented ϵ-constraint method to generate a set of non-dominated solutions. Two numerical examples are used to demonstrate the feasibility of the model and solution algorithm. For the hypothetical numerical example based on the bike-way network of Jurong Lake district in Singapore, four alternative non-dominated bike-way design plans are generated.